ANALYSIS OF TOTAL FLAVONOID LEVELS OF ETHANOL EXTRACT (Cinnamon (Cinnamomum burmanii Blume) LEAVES WITH UV-VIS SPECTROPHOTOMETRY METHOD - P, Darmayuda I P; G, Suardana I; A. A, Bawa Putra (Jurnal Ilmu Pendidikan Indonesia, 2021)
Cinnamon plants (Cinnamomum burmani Blume), including plants that have medicinal properties for diabetes mellitus because they contain flavonoid compounds. This study aimed to determine the total flavonoids content of the ethanol extract of cinnamon leaf ethanol extract using UV-Vis spectrophotometry method. The ethanol extract of Cinnamon leaf was obtained by maceration using ethanol as a solvent.The qualitative analysis used FeCl3by forming yellowish green complex. The determination of total flavonoids content is conducted basedon AlCl3method with total flavonoidse xpressed in QE (Quercetin equivalent) at the maximum wavelength of 435 nm. The result showed that the average content of flavonoid total is 19.544 mg QE/g extract.